Sales Transaction Data Analysis using Apriori Algorithm to Determine the Layout of the Goods - Hariguna, Taqwa; Hasanah, Uswatun; Susanti, Nindi Nofi (International Journal of Informatics and Information Systems, 2018)
In a shop, usually apply a sales strategy in order. The sales strategy can be in the form of determining the layout of goods so that they are close to one another. Determining the layout of items can be based on items that are often purchased simultaneously. Searching for items that are often purchased together can be done using data mining techniques, which is processing data to become more useful information. Sales transaction data processing can be done using apriori algorithm. Apriori algorithm is the most famous algorithm for finding high-frequency patterns and generating association rules. From the results of the discussion and data analysis, there were 3 (three) association rules formed, namely